PATIENT PERCEPTION ON PHYSICIAN PRACTICE WHILE PRESCRIBING FOR RADIOLOGY EXAMINATION - SURESH SUKUMAR (International Journal of Pharma and Bio Sciences, 2015)
Patient perception on physician practice while prescribing for radiology examination .our objectives is to assess the patient perception of physician practice and to assess the patient’s perception on radiologic examination. The study was conducted from February 2014 to April 2014 in South Kanara District of Karnataka (rural 65.2%, n-326 and urban 34.8%, n-174). The patient referred from the department of orthopedists and medicine to the radiology department are considered for the study. The selections of the patients are based on the convenience sample. The prospective study design approach was considered for the study. In this study i had developed 15 items forming two domains using frequency four point scales with nine items and Likert five point scales with six items, to assess the patient perception of physician practice and the patient perception on radiologic examination.to analysis the data obtained from our questionnaire study we considered the descriptive static analysis and Pearson chi square test. The descriptive static analysis used to analysis the demographic chart of the patient and items. The Pearson chi square test was used to determine the association between the (a) educations of the patient and radiation awareness, (b) previous radiology examination and knowledge about radiation, (c) previous radiology examination and protective device used in radiology examination, (d) previous radiology examination and signage’s used in radiology department. The outcome of our study shows that referring physician follows poor justification ofpractice. The majority of the physicians (75.0%) do not explain the importance of radiology examination to the patient. Only 1.2% of research population had agreed that the referring physician always explains or discuss the relevance of radiology examination prescribed to the diagnosis of the patient specific condition.The majority of the research population had reported that referring physician does not explain the risk (91.4%) and benefit (87.4%) associated with the radiology examination were radiation is used. Minority of research population had strongly agreed that they were comfortable when referring doctors informing about the risk (12.6%) and benefit (11.6%) from radiology examination. The most interesting outcome of the study shows that 88.2% of the referring physician never resists the patient wish to undergo the radiology examination when it is not necessary. In present study there is a poor communication between the medical practitioner and patient while prescribing for the radiology examination. The outcome of the study also shows that Patient who were undergoing the radiology examination had poor knowledge about the radiation and get very less or no information about the benefit, risk and dose involved in radiologic examination from the prescribed doctors.